Binding of the 9-O-N-aryl/arylalkyl Amino Carbonyl Methyl Substituted Berberine Analogs to tRNAphe - Basu, Anirban; Jaisankar, Parasuraman; Suresh Kumar, Gopinatha (PLOS ONE, 2013)
Background Three new analogs of berberine with aryl/arylalkyl amino carbonyl methyl substituent at the 9-position of the isoquinoline chromophore along with berberrubine were studied for their binding to tRNAphe by wide variety of biophysical techniques like spectrophotometry, spectrofluorimetry, circular dichroism, thermal melting, viscosity and isothermal titration calorimetry. Methodology/Principal Findings Scatchard binding isotherms revealed that the cooperative binding mode of berberine was propagated in the analogs also. Thermal melting studies showed that all the 9-O-N-aryl/arylalkyl amino carbonyl methyl substituted berberine analogs stabilized the tRNAphe more in comparison to berberine. Circular dichroism studies showed that these analogs perturbed the structure of tRNAphe more in comparison to berberine. Ferrocyanide quenching studies and viscosity results proved the intercalative binding mode of these analogs into the helical organization of tRNAphe. The binding was entropy driven for the analogs in sharp contrast to the enthalpy driven binding of berberine. The introduction of the aryl/arylalkyl amino carbonyl methyl substituent at the 9-position thus switched the enthalpy driven binding of berberine to entropy dominated binding. Salt and temperature dependent calorimetric studies established the involvement of multiple weak noncovalent interactions in the binding process. Conclusions/Significance The results showed that 9-O-N-aryl/arylalkyl amino carbonyl methyl substituted berberine analogs exhibited almost ten folds higher binding affinity to tRNAphe compared to berberine whereas the binding of berberrubine was dramatically reduced by about twenty fold in comparison to berberine. The spacer length of the substitution at the 9-position of the isoquinoline chromophore appears to be critical in modulating the binding affinities towards tRNAphe.